Pendampingan UMKM dalam Pemanfaatan Digital Marketing untuk Peningkatan Daya Saing Usaha - Leonardo Indra Vitaharsa; Elly Agustina Julisawati (Jurnal Ragam Pengabdian, 2025)
This community service program aims to assist micro, small, and medium enterprises (MSMEs) in utilizing digital marketing as a strategy to enhance business competitiveness. MSME partners in Cipinang Melayu received training on digital branding concepts, content creation practices, social media management, and marketplace utilization. The results indicated a significant improvement, with social media followers increasing by 25–40% within two weeks and greater consumer interactions through WhatsApp Business. These findings demonstrate that digital marketing is an effective strategy for expanding market reach, boosting sales, and strengthening business image. Moreover, the program raised awareness among MSMEs about the importance of digital literacy for business sustainability.